Psychiatric features in perpetrators of homicide-unsuccessful-suicide at Weskoppies Hospital in a 5-year period - Paul Sussman; Carla Kotze (South African Journal of Psychiatry, 2013)
Background. In the absence of medical literature reporting on homicide-unsuccessful-suicide (HUS) cases in which the perpetrator is referred for forensic psychiatric observation present an opportunity to explore psychiatric features pertaining to the event.